Adjuvant Chemotherapy Might Be Recommended to Patients With Positive Margin After Gastrectomy: A 20-Year Retrospective Analysis in a Single Center - Zhang, Xiaojie; Zhao, Lulu; Niu, Penghui; Wang, Tongbo; Wang, Wanqing; Sun, Chongyuan; Li, Zefeng; Chen, Yingtai; Zhao, Dongbing (Frontiers in Oncology, 2022)
Background: Margin positivity after gastric cancer resection is associated with poorer outcomes. However, the prognostic factors and the choice of postoperative adjuvant treatment of patients with positive margin (PM) after gastrectomy are still being debated. Methods: A single-center, retrospective analysis was conducted for patients with PM after gastrectomy from the China National Cancer Center Gastric Cancer Database (NCCGCDB) from 1998 to 2018. Univariate and multivariate Cox regression analysis was performed to identify prognostic factors of overall survival (OS) and recurrence free survival (RFS). Results: A total of 449 patients were included in the study, including 192 (42.8%) in the proximal positive margin group (PPM), 205 (45.7%) in the distal positive margin group (DPM), and 52 (11.6%) in the bilateral positive margin group (BPM). The 3- and 5-year OS rates for the PM patients investigated were 47.5% and 39.3%, respectively, and the 3- and 5-year RFS rates were 60.0% and 53.6%, respectively. Multivariate Cox regression analysis proved total gastrectomy (P=0.012), pT4 stage (P=0.01), pN2 stage (P=0.016), pN3 stage (P=0.009) and combined resection (P=0.003) to be independent risk factors of OS，and pT3 stage (P=0.036) and pT4 stage (P=0.020) were independent risk factors for RFS. Adjuvant chemotherapy prolonged OS in PPM group (P=0.032) and prolonged RFS in PPM group (P<0.001) and DPM group (P=0.035) compared to surgery alone. Conclusions: Advanced pathologic stage was associated with poor prognosis and postoperative adjuvant chemotherapy might be recommended in PM patients after gastrectomy. Still, further prospective trials are warranted to verify and support our conclusions.